Evaluation of circulating cytokine concentrations and ex vivo indicators of the inflammatory response in transition dairy cows fed pre- and postpartum diets differing in metabolizable protein supply - Trent A. Westhoff; Anja S. Sipka; Thomas R. Overton; Suzanne Klaessig; Sabine Mann (Journal of Dairy Science)
ABSTRACT: The nutrient deficit during the transition period might alter activity of the nutrient-sensing mechanistic target of rapamycin, thereby influencing immune phenotype and the inflammatory balance of transition cows. We investigated changes in circulating markers of inflammation during the transition period. Additionally, we assessed changes in ex vivo indicators of the whole blood leukocyte cytokine response to LPS stimulation and leukocyte phagocytosis and oxidative burst. The second objective was to determine whether increasing the MP supply in the prepartum, the postpartum, or both diets would affect the measured parameters. Multiparous Holstein cows (n = 96) were assigned to 1 of 4 treatment groups at 28 d before expected calving following a randomized block design. Prepartum diets were formulated to contain either a control (85 g MP/kg DM) or high (113 g MP/kg DM) level of estimated MP. Postpartum diets were formulated to contain either a control (104 g MP/kg DM) or high (131 g MP/kg DM) level of estimated MP. To control the potential confounding effect of Met and Lys supply, diets were formulated to supply an equal amount at 1.24 and 3.84 g/Mcal of ME in both prepartum diets and 1.15 and 3.16 g/Mcal of ME in both postpartum diets, respectively. The combination of a pre- and a postpartum diet resulted in treatment groups: control-control (CC), control-high (CH), high-control (HC), and high-high (HH). Serum concentrations of tumor necrosis factor (TNF), IL-10, and IFN-γ were determined at −6, 3, 10, and 21 d relative to calving using a multiplex assay. Complete blood cell count, whole blood cytokine response to LPS stimulation, and PMN and peripheral blood mononuclear cell (PBMC) phagocytosis and oxidative burst were determined at −28, −10, 7, and 21 d relative to calving. Serum concentrations of TNF were below the lower limit of detection (≤12 pg/mL) in 282 (75.4%) samples. Serum concentrations of IL-10 and IFN-γ were greatest at −6 d relative to calving. Serum concentrations of IFN-γ did not differ by treatment, but IL-10 was greater in CH compared with HH and HC at 10 and 21 DIM, respectively. Compared with CC, white blood cell counts were 13.9% higher in HC, granulocyte counts were 17.6% and 14.7% higher in CH and HC, respectively, and monocyte counts were 27.4% higher at 7 DIM in HC. Lymphocyte counts were 12.7% and 13.9% higher in HC compared with CC and CH, respectively. Phagocytic ability and oxidative burst of PMN and PBMC did not differ by treatment. Whole blood LPS–induced IL-10 and TNF concentrations increased to a greater extent at 7 DIM and 7 and 21 DIM compared with −10 d relative to calving, respectively, and similarly in all treatments. In summary, whereas serum IL-10 and IFN-γ concentrations were greatest during late gestation, whole blood LPS–induced cytokines and phagocytosis increased to a greater extent during early lactation, suggesting a robust inflammatory response. However, increasing the MP supply during the transition period did not meaningfully influence indicators of the inflammatory response.